(untitled) (International Journal of Engineering and Computer Science, 2015)
In this paper to investigate the effect of Electrolytic Capacitor and Ultra Capacitor The electrolytic capacitor produces distortion in output while ultra capacitor produces distortion less output. By way of habit DSTATCOM & Tuning the block Parameter of Controller by using matlab Simulation. The foremost detached of the research paper is to appearance that using DISTRIBUTION STATCOM (DSTATCOM) it is possible to reduce the voltage fluctuations like drop and fabulous conditions in distribution systems. In this paper diverse topologies of DSTATCOM (distribution static compensator) are discussed. The distribution static compensator (DSTATCOM) is a shunt connected device capable of compensating power quality problems in the load current. A shunt active filter intended for installation on a power distribution system. The active filter has an addition a capability to regulate the distribution line voltage by means of adjusting reactive power. Theoretical analysis investigates the dynamic performance of combined harmonic damping and voltage regulation. As a result, harmonic damping makes it possible to improve the stability of the control loop for voltage regulation, and the combined harmonic curbing. The system with control scheme is implemented in Matlab / Simulink. The simulation results are shown in figures. The main detached of the research paper is to show that using (DSTATCOM) it is possible to reduce the voltage fluctuations like fall and marvelous conditions in distribution systems